Analisis Penggunaan Variable Speed Drive (VSD) pada Motor Kompresor - Tresna Umar Syamsuri; Harrij Mukti K.; Rohmanita Duanaputri (Elposys: Jurnal Sistem Kelistrikan, 2021)
A Variable Speed Drive (VSD) is a device that regulates the speed and rotational force or torque of mechanical equipment. VSD improves efficiency by allowing the motor to operate at the ideal speed for each load condition. In many applications, VSD reduces the electricity consumption of the motor by 30-60%. The energy-saving potential of electric motors is significant as motor systems account for more than 60% of the power consumed by industries. It is due to these advantages that VSD can be used to control the speed of compressor motors, thereby enhancing the performance of the compressor. A compressor motor is a device that compresses air and increases its pressure. To compress air, the compressor requires a driving force, and one of them is the motor. When the output air pressure of the compressor exceeds a certain value, the relief valve will open automatically, allowing the air to remain in the tank even when the motor is still running. During compressor operation, the motor is always started with a high starting current, resulting in high power demand. Therefore, control of the compressor motor is necessary.